A critical overview of the Area Studies model: A brief study of the current trends in Area Studies - Alexander, Andrew (Cappadocia Journal of Area Studies, 2020)
Since its inception in the colonial era, Area Studies (AS) has evolved in accordance with policy-oriented demands. From the study of former colonial territories to strategic areas of the Cold War, and from September 11, 2001 through to the present day, this academic field has been entangled with government, with an impetus aimed at achieving policy goals. Using the seminal book Middle East Studies after September 11: Neo-Orientalism, American Hegemony and Academia as its basis, we present here a critical examination of historical context of the evolution of Area Studies and the current trends in the field. Some of the notable current trends in the field include observable rotations in area focus that over the last decade have manifested in a geospatial shift of focus to East Asia by US-centric academia, and the adoption of AS as a model outside of the United States and Europe. Regarding the latter, this brief study investigates the adaptation of an AS model by China, noting the transference of the practical negative attributes of AS, and critically engages in the AS dialectic by asking the question of whether the colonial, imperialist and Orientalist history and attributes of AS are inherent to the field when adopted by actors from outside its traditional milieu.